Mechanochemical Gold(III)‐Carbon Bond Formation. Issue 24 (6th May 2021) - Eppel, Daniel; Eryiğit, Alpay; Rudolph, Matthias; Brückner, Margit; Rominger, Frank; Asiri, Abdullah M.; Hashmi, A. Stephen K.
Abstract: Starting from a [( MeO C^N^C)AuCl] complex as precursor, a direct substitution by C, H‐activation from sp‐, sp 2 ‐ or sp 3 ‐C, H‐bonds under basic conditions in a planetary ball mill was achieved. Because of the extraordinary photophysical properties of the target compounds, this protocol provides an easy access to a highly valued complex class. In contrast to existing protocols, no pre‐functionalization of the starting materials is necessary and the use of expensive transition metal catalysts can be avoided, which makes this application appealing also for industrial purposes. In addition the methodology was not restricted to pincer complexes, which was demonstrated by the substitution of chelate type [(tpy)AuCl2 ] complexes. Abstract : The mechanochemical conversion of gold(III) complexes with sp‐, sp 2 ‐, sp 3 ‐C, H bond‐containing substrates in a planetary ball mill is reported. The base supported reaction delivers high valued products under solvent‐free and mild reaction conditions.